Moods and Modality in Virtual Communication: The Study of Multimodal Analysis in Teaching Practice - Asnawi; Amrin Saragih; Rahmad Husein (Association of Language Teachers in Southeast Asia (ALTSA), 2023)
The focus of the study was on moods and modality in virtual communication. The purposes of the research were to analyze the moods and modalities used by the lectures for virtual teaching to evaluate the manner of the moods and modalities realized in virtual teaching and to investigate reasons underlying the use of moods and modalities in virtual teaching. The sources of data for this research were verbal and nonverbal language from the interactions of virtual teaching. The data were utterances and gestures produced by the lecturers. The research design was qualitative research. The data were collected through recorded videos, observations, interviews, and questionnaires. The techniques of analyzing the data were applying interactive data analysis: data condensation, data display, and drawing and verification conclusion. It was found that the lectures used various kinds of moods. The declarative mood was dominantly used. In terms of modality, both modalization and modulation types of modality were used. The value of the modality selected was low, medium, and high. The manner of the mood system was realized by both marked and unmarked ones. The modalities were realized through the integration of verbal and verbal modalities. The modalities were used to manage the classroom and create a pleasant and understandable teaching and learning atmosphere. The result of this study gives a new insight into the function of language in teaching through online mode.